THE FIRST PHOTOGRAPHS OF THE VILLAGE KUBACHI - Magomedov, A Dz (History, Archeology and Ethnography of the Caucasus, 2016)
Photography is an important part of historical and information culture of the society. It originally emerged as a new technology and has become an authentic art and part of the culture. Its documentary importance (photos, figures, etc.) for study of the history of art and culture is great. In particular, it is referred to the first photos of the village Kubachi and its architectural forms. These pictures were taken by the outstanding Georgian photographer A.Roinashvili and the famous Frenchman F.O rden in 1880-1890. However, A.Roinashvili’s authorship of the photos of Kubachi is doubtless, while F. Orden’s works relating to Dagestan require further study.
Keywords: photography; first photos of Dagestan; Kubachi; A.Roinashvili; photographer F.Orden